2005
DOI: 10.1097/01.sla.0000164179.48276.45
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Surgery Malpractice Risk

Abstract: These data demonstrate no increased risk of lawsuit when caring for trauma patients, and the actual risk of a malpractice lawsuit was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…The orthopedic claim data presented here derive mainly from intraoperative adverse events and mainly focus on elective orthopedic surgery. Traumatology accounts for only 25% of the claims, in good agreement with the findings of previous studies [ 7 ], possibly because of lower preoperative expectations of acute and hyperacute patients [ 16 ]. Indeed, it is believed that the most important reason for malpractice claims is a large negative disparity between the preoperative expectations of the patient and the postoperative results for that patient [ 7 , 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…The orthopedic claim data presented here derive mainly from intraoperative adverse events and mainly focus on elective orthopedic surgery. Traumatology accounts for only 25% of the claims, in good agreement with the findings of previous studies [ 7 ], possibly because of lower preoperative expectations of acute and hyperacute patients [ 16 ]. Indeed, it is believed that the most important reason for malpractice claims is a large negative disparity between the preoperative expectations of the patient and the postoperative results for that patient [ 7 , 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…In a review of three prospectively maintained databases comparing elective, urgent, and emergent cases in a general surgery practice, Stewart noted similar rates of claims filed per procedure performed for each surgical classification. 15 In a review of cases filed against one physician owned malpractice carrier in New York, Rovit et al 3 found that only 5% of spine cases arose from traumatic injuries. However, Agarwal et al 10 noted that claims arising after trauma represented 31.4% of cases in his review.…”
Section: Resultsmentioning
confidence: 99%
“… Mean indemnity payments for cases concluding in plaintiff’s verdict or settlement. 6 , 7 , 9 , 12 , 15 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…Other authors have mentioned a misbalance in expectations before surgery and the result that follows [ 10 , 30 ]. This could very well explain the fact that most surgical claims are related to an elective procedure, since in acute setting expectations might be lower [ 31 ].…”
Section: Discussionmentioning
confidence: 99%